Kajian dan Analisis Mutu Pupuk Organik Padat Ngremboko Berdasarkan Standar Nasional Indonesia (SNI 7763:2018) - Dian Kresnadipayana; Dionysius Andang Arifwibawa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was evaluate the quality of Ngremboko organic solid fertilizer based on chemical, biological, and heavy metal parameters in accordance with the Indonesian National Standard (SNI) 7763:2018. Materials and methods. The research employed a laboratory-based experimental method with descriptive quantitative analysis. Testing was conducted at the BPSMB Surakarta Testing Laboratory, which is accredited by the National Accreditation Committee (KAN). Results. The results showed that Ngremboko organic fertilizer contained 19.24% organic carbon, a C/N ratio of 7.54, a moisture content of 20.60%, and macronutrient levels of nitrogen (N) 2.55%, phosphorus (P₂O₅) 0.65%, and potassium (K₂O) 2.99%. Microbiological contamination by Escherichia coli and Salmonella sp., as well as heavy metal concentrations, were below the maximum permissible limits. Overall, all evaluated parameters met the quality requirements of SNI 7763:2018. Conclusions. These findings indicate that Ngremboko organic solid fertilizer is safe, effective, and suitable for use in sustainable agricultural practices.